Production economics estimation on hop farms - Pavlovič, Martin (Hmeljarski bilten, 2025)
Hops are international trading commodity in agricultural markets. As per acreage of hops - Slovenia is positioned in 2025 as the 5th country on a global hop market. Farmers may acquire accurate estimate of production costs and gross margin (EUR/ha) by participating on workshops for benchmarking of economics at farm level. On workshops in 2025 input data about cultivation technology and production costs as well as revenues related to production and marketing of hops were analyzed from 10 farms for the 2024 growing season. In the paper we illustrate the three key economic parameters related to competitive value of hop farms analyzed. The average group revenue amounted 10,463 EUR/ha, the average group variable costs were assessed as 6,476 EUR/ha and the average gross margin was calculated as 4,169 EUR/ha. The included farmers acknowledged benefits and have thus accepted for the fourth time (since 2021) the presented method of a group assessment of hop production economics at farms level.
Keywords: analiza stroškov; costs analysis; farms; gross margin; hmelj; hmeljarstvo; hop; hop industry; kmetije; model PKH; pokritje